2002
DOI: 10.1002/1521-4141(200208)32:8<2105::aid-immu2105>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Peptide analysis, stability studies, and structural modeling explain contradictory peptide motifs and unique properties of the NOD mouse MHC class II molecule H2-Ag7

Abstract: The MHC class II molecule H2‐Ag7 is the chief genetic determinant in insulin‐dependent diabetes mellitus of the non‐obese diabetic (NOD) mice. Poor peptide binding ability, as well aspresentation of a unique subset of peptides by this molecule was suggested to promote autoimmunity in this strain. However, several laboratories have presented results in favor of an H2‐Ag7 molecule that can avidly bind many different peptides. The crystal structures of H2‐Ag7 in complex with two different peptides did not complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…These conclusions were further bolstered by previous work from different laboratories, demonstrating that the diabetogenic class II MHC molecules, were unstable in SDS, i.e. they dissociated into the α-and β-subunits under non-denaturing conditions [13,[16][17][18][19][20][21]. Prior work with other alleles, such as I-A k or I-A b , had established a clear correlation between SDS stability and peptide quality: high affinity peptides formed SDSstable heterodimers, while low affinity peptides did not [16,22,23].…”
Section: Biochemical Structural and Functional Properties Of Diabetementioning
confidence: 75%
See 2 more Smart Citations
“…These conclusions were further bolstered by previous work from different laboratories, demonstrating that the diabetogenic class II MHC molecules, were unstable in SDS, i.e. they dissociated into the α-and β-subunits under non-denaturing conditions [13,[16][17][18][19][20][21]. Prior work with other alleles, such as I-A k or I-A b , had established a clear correlation between SDS stability and peptide quality: high affinity peptides formed SDSstable heterodimers, while low affinity peptides did not [16,22,23].…”
Section: Biochemical Structural and Functional Properties Of Diabetementioning
confidence: 75%
“…We and others have noted that I-A g7 -bound peptides contain multiple C-termini acidic residues that contribute towards binding affinity [17,24]. More importantly, >80-90% of peptides isolated from I-A g7 contain C-terminal stretches of two or three acidic residues [24,25] (Figure 1).…”
Section: Biochemical Structural and Functional Properties Of Diabetementioning
confidence: 93%
See 1 more Smart Citation
“…Although in appearance IA g7 and HLA-DQ8 appear similar, yet there are subtle differences that may affect peptide binding and T-cell recognition. 42 IA g7 has a pH-dependent peptidebinding motif concerning pockets 6 and 9 arising largely from the presence of three histidines in proximity of these pockets (a68, b9 and b56), whereas DQ8 shows a higher binding affinity for peptides at endosomal pH, but no change in motif.…”
Section: Discussionmentioning
confidence: 99%
“…DQ8 in comparison to I-A g7 has some distinct features, particularly at P4 in which large residues are favored (26). Examination of naturally processed peptides bound to I-A g7 of APCs showed that ϳ80 -90% contained from one to three acidic residues at the carboxyl end (23,24,27,28). As predicted from the structural analyses (19,25), there was binding cooperativity among acidic residues at P9, P10, or P11 (23).…”
Section: The Insulin B:(9 -23) Peptide Binds Weakly To I-a G7mentioning
confidence: 94%